Impact of exercise video-guided bodyweight interval training on psychophysiological outcomes in inactive adults with obesity - Bellissimo, Gabriella F.; Bailly, Alyssa; Bourbeau, Kelsey; Mermier, Christine; Campitelli, Anthony; Berkemeier, Quint; Specht, Jonathan; Smith, Jessica; Ducharme, Jeremy; Stork, Matthew J.; Little, Jonathan P.; Kravitz, Len; et al. (Frontiers in Physiology, 2025)
PurposeDetermine the impact of a 6-week YouTube-instructed bodyweight interval training (BW-IT) program on cardiometabolic health, muscular strength, and factors related to exercise adherence in adults with obesity.MethodsFourteen adults (30.7 ± 10.3 yrs, BMI 35.5 ± 5.4 kg/m2) participated in this study. The BW-IT program progressed bi-weekly from a 1:3 to 1:1 work-to-rest ratio, using maximum effort intervals of high knees, squat jumps, scissor jacks, jumping lunges, and burpees. Pre- and post-intervention measures included peak oxygen consumption (V˙O2peak), relative quadriceps isometric muscular strength, waist circumference (WC), body composition via bioelectrical impedance, and cardiometabolic blood markers (blood glucose, insulin, lipid panel, and C-reactive protein). Self-efficacy (task and scheduling) and physical activity enjoyment (PACES) were also assessed.ResultsRelative isometric muscular strength increased by 12.5% (p = 0.02, dz 0.4) and absolute V˙O2peak by 4.2% (p = 0.03, dz = 0.2). WC reduced by 2.1% (p < 0.001, dz = 0.2). Task self-efficacy was similar pre- to post-intervention (p = 0.53, dz = 0.2), while scheduling self-efficacy was reduced (p < 0.004, dz = 1.1). PACES scores were 9.6% higher week one compared to week six of BW-IT (p = 0.003, dz = 0.6). No changes occurred in body composition or cardiometabolic blood markers.ConclusionIn previously inactive adults with obesity, 18 sessions of YouTube-instructed bodyweight interval training elicited small to moderate effects on lower extremity muscular strength, cardiorespiratory fitness, and waist circumference. Future studies may benefit from longer interventions and adding a greater variety of calisthenics to determine interventions that improve physiological health and maintain or enhance factors associated with exercise adherence.